2019
DOI: 10.3389/fmars.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Flipping for Food: The Use of a Methane Seep by Tanner Crabs (Chionoecetes tanneri)

Abstract: Methane seep habitats are widespread chemosynthesis-based ecosystems that span continental margins and interact with surrounding marine systems. With many of these habitats occurring below 200 m, seeps can serve as an important source of nutrients in otherwise food limited deep-sea environments. However, the potential for marauding megafauna to assimilate seep derived nutrition has been difficult to quantify. Here, we provide the first evidence of a commercially harvested species, Chionoecetes tanneri (tanner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 78 publications
(99 reference statements)
1
36
0
Order By: Relevance
“…In addition, US Atlantic margin seeps can provide trophic support to commercially important red crab populations and some seeps may act as a reproductive hotspot for red crabs. Numerous studies have found commercially important species to be present at seep ecosystems but few studies discuss trophic (Seabrook et al, 2019; this study) or reproductive (this study) connections between seeps and commercial species, suggesting that this is a fruitful area for future research. Given the hundreds of unexplored methane seeps on the US Atlantic margin, continued exploration will build a more complete picture of the ecosystem services provided by methane seeps.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, US Atlantic margin seeps can provide trophic support to commercially important red crab populations and some seeps may act as a reproductive hotspot for red crabs. Numerous studies have found commercially important species to be present at seep ecosystems but few studies discuss trophic (Seabrook et al, 2019; this study) or reproductive (this study) connections between seeps and commercial species, suggesting that this is a fruitful area for future research. Given the hundreds of unexplored methane seeps on the US Atlantic margin, continued exploration will build a more complete picture of the ecosystem services provided by methane seeps.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, a comparison of stable isotope methodologies has suggested bulk stable isotope analysis (as used here) may underestimate the role of chemosynthetically-derived nutrition in seep-associated fauna (Seabrook et al, 2019). At methane seeps off British Columbia (Canada), seep-associated bacteria were identified as dietary sources for tanner crabs (Chionoecetes tanneri) based on fatty acid analysis and molecular analysis of stomach contents, while carbon isotope values of the leg muscle suggested the species relied solely on photosyntheticallyderived carbon (Seabrook et al, 2019). Differing results between compound specific fatty acid analysis and bulk stable isotope analysis may be explained by the amount of time needed for muscle tissue to reflect the isotopic composition of the food ingested (Seabrook et al, 2019).…”
Section: Red Crab Autecologymentioning
confidence: 99%
See 3 more Smart Citations